THORACIC SEGMENTAL SPINAL ANAESTHESIA IN UPPER ABDOMINAL SURGERIES AND SIMPLE MASTECTOMY-A CASE SERIES - BORAH, MADHUCHANDA; DAS, KAVERI; AHIR, BIJOY; VERMA, ANJALI; GOWTHAM, PYDIMALLA VENKATA; DAS, KARUNA KUMAR; BARUAH, PRITANU DEB (International Journal of Current Pharmaceutical Research, 2024)
Objective: To observe safety and efficacy of Segmental thoracic spinal anesthesia (STSA) in upper abdominal and breast surgeries. Methods: 14 cases were selected, out of which 6 laparoscopic cholecystectomy (LC), 4 open cholecystectomy (OC), 3 emergency exploratory laparotomy and 1 simple mastectomy. Under full aseptic precaution, segmental thoracic spinal anesthesia was administered through midline approach in T8-9 space for upper abdominal surgeries and T5-6 space in a simple mastectomy. Using 25G Quincke spinal needle 1.5 ml [7.5 mg] of 0.5% Isobaric Levobupivacaine mixed with 0.4 ml (20µg) Fentanyl was given in abdominal surgeries and 1.2 ml [6 mg] of 0.5% Isobaric Levobupivacaine mixed with 0.4 ml (20µg) Fentanyl in simple mastectomy. Results: Age group of patients ranged from 25 to 65 y, Male: Female ratio of 4:10, Body Mass Index (BMI) range of 22 to 24.9 with physiological status of ASA I to ASA III. Hemodynamically, hypotension was observed in every patient after 5-10 min of STSA well managed with fluid and vasopressors with no bradycardia. Average width of sensory block was T3 to L1-2 in upper abdominal surgeries and T1 to T8 in a simple mastectomy. Motor block was Modified Bromage Scale (MBS) of 0 to 1 during and postoperatively. Regarding analgesia, Visual Analogue Scale (VAS) score was 0 intraoperatively and 0-1 postoperatively. Sedation score was 2 both intraoperatively and postoperatively with no significant complications and good patient and surgeon satisfaction. Conclusion: Segmental thoracic spinal anaesthesia is a safe and effective procedure with good patient and surgeon satisfaction.